The meaning of aboriginal control of education under current self-government agreements in Canadá - Paquette, Jerald (Universidad de Antioquia, 2011)
The Department of Indian Affairs and Northern Development (DIAND)-imposed band-council governance at the community level aligns with the seductive delusion popularized and given credence by Indian Control of Indian Education (ICIE) (National Indian Brotherhood, 1972/1984) that “Indian control” is synonymous with “local control,” a belief that has taken on mythic proportions over the years despite the paradox that most First-Nations are too small ever to operate an “education system” in any meaningful sense. This paper reviews the meaning and content of various aboriginal self-government discourses that have emerged over the last 30 years. Based on a detailed policy-theme analysis of policy papers, reports, and various self-governance agreements on this issue of First Nations control of education, this paper presents a network of interlocking concepts and models that provides a coherent and defensible understanding of the current state of aboriginal rights to control of education while mapping various forms of institutional arrangements or internal principles of organization for self-determination that have emerged over time in discourse on aboriginal rights and education in Canada. En Canadá, los gobiernos de Consejos de Banda a nivel comunitario fueron impuestos por el Departamento de Asuntos Indígenas y Desarrollo del Norte, mediante la seductora ilusión, popularizada y acreditada por el documento “Control indígena de la educación indígena”, de que “control indígena” es sinónimo de “control local”, una idea que ha tomado proporciones míticas a los largo de los años, no obstante la paradoja según la cual la mayoría de las Primeras Naciones son demasiado pequeñas para administrar un “sistema educativo” en sentido estricto. Este artículo revisa el significado y el contenido de varios discursos sobre el autogobierno aborigen que han emergido en los últimos treinta años. Con base en un detallado análisis normativo de documentos, reportes y varios acuerdos de autogobierno relacionados con el tema del control ...